Les Femmes anishinaabeg (Canada), la santé et l’eau : des savoirs traditionnels aux mobilisations contemporaines - Castelli Tania; Thinel Myriam; Cantin Alex-Andrée; Patrick Cloos (Amnis)
Access to quality drinking water is a fundamental right. Despite Canada's wealth of fresh water, many First nations, including the Anishinaabeg, regularly face inequitable access to quality drinking water, a situation that has health, spiritual and cultural consequences. These injustices are a direct result of colonization and the unequal relationship between the Canadian government and First Nations, which has greatly contributed to restricting the traditional role of Anishinaabeg women as water protectors, despite their spiritual and identity connection to water. Nevertheless, these women have shown resilience, which is reflected in a number of initiatives to raise awareness, mobilize and advocate for water protection. In this article, we seek to show that an ecological and sanitary issue, such as the availability of quality drinking water for Indigenous peoples in Canada, is part of a power struggle, past and present, with the federal government and the provinces. Our article aims more specifically at : 1) showing the importance of the lack of availability of drinking water for Indigenous nations ; 2) describing the traditional role of Anishinaabeg women as water protectors ; 3) situating the water issue in its colonial context ; and 4) exploring the various mobilizations led by Indigenous women in response to this historical and political problem.